Experimental study of the influence of adhesive properties and bond length on the bond behaviour of NSM FRP bars in concrete - Torres, Lluís; Sharaky, Ibrahim Attia; Barris, Cristina; Baena, Marta (Journal of Civil Engineering and Management, 2016)
The near-surface mounted (NSM) fibre reinforced polymer (FRP) technique is a relatively recent system for strengthening concrete structures. Bond is a key factor in its behaviour, and is affected by many factors whose influence can only be tested through experimental studies. In this study, the modified pull-out test was used to study the effect of epoxy properties and bond length on the behaviour of NSM FRP bars. Three epoxy types, two FRP materials (carbon and glass) and four bond lengths (6db, 12db, 24db and 30db) are used. The load capacity, slips at the loaded end and free end and average bond stress are all analysed. The test results indicate that the role of epoxy properties appear to be a key factor in bond performance in the NSM FRP strengthening technique, and that their effect varies depending on bond length and FRP properties.